2021
DOI: 10.3389/fphar.2021.731980
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Small Ubiquitin-Like Modifier 2 and Protein SUMOylation as a Cardioprotective Mechanism Against Myocardial Ischemia-Reperfusion Injury

Abstract: Background: Small ubiquitin-like modifier (SUMO) proteins modify proteins through SUMOylation as an essential protein post-translational modification (PTM) for regulating redox status, inflammation, and cardiac fibrosis in myocardial infarction. This study aimed to investigate whether natural product puerarin could alleviate myocardial ischemia/reperfusion injury (MI-RI) by targeting protein SUMOylation.Methods: Mouse MI-RI model was induced by ligating the left anterior descending (LAD) coronary artery and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For animal experiments, the sample size was calculated using the formula: Sample size = 2* SD2 (Zα/2 + Zβ) *2 /d2. It was previously demonstrated that the mean myocardial infarction area was 16.32% for mice model and 6.85% for sham groups while SD is 6.45% [34]. When the level of significance at 5% and power of study at 80% were selected for two tailed unpaired t -test, the sample size = 2* (6.45)2* (1.96 + 0.842) *2 / (9.47)2 = 5.2.…”
Section: Mouse Model Of Myocardial Ischemiareperfusion Injury (Miri)mentioning
confidence: 95%
See 1 more Smart Citation
“…For animal experiments, the sample size was calculated using the formula: Sample size = 2* SD2 (Zα/2 + Zβ) *2 /d2. It was previously demonstrated that the mean myocardial infarction area was 16.32% for mice model and 6.85% for sham groups while SD is 6.45% [34]. When the level of significance at 5% and power of study at 80% were selected for two tailed unpaired t -test, the sample size = 2* (6.45)2* (1.96 + 0.842) *2 / (9.47)2 = 5.2.…”
Section: Mouse Model Of Myocardial Ischemiareperfusion Injury (Miri)mentioning
confidence: 95%
“…Natural products ginkgolic acid and astragaloside IV were also evaluated for targeting SUMOylation of proteins in animal models of MI and cell culture systems [32,33]. Along this line, we previously demonstrated that plant-derived C-glycosylated isoflavone puerarin exhibited effective cardioprotective potential in a mouse model of myocardial infarction via enhancing SUMO2-mediated SUMOylation without affecting SUMO1 expression [34]. However, little is known about the protein substrates that are SUMOylated by SUMO2 in myocardial infarction.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Mouse Hearts were cut into 1 cm-thick sections and stained with 2,3,5-triphenyl tetrazolium chloride (TTC) (Sigma Aldrich, Saint Louis, MO, United States) as previously described (Zhao et al, 2021). In brief, five pieces of heart sections were immersed in 2% TTC solution and incubated at 37 °C for 20 min.…”
Section: Assessment Of Infarct Sizementioning
confidence: 99%
“…PPARγ plays a key role in physiological and pathological processes of renal fibrosis. The reduction of PPARγ SUMOylation suppresses the activation of anti-apoptotic and anti-inflammatory cytokines through inhibiting the NF-κB activity (Xie et al, 2018;Zhao et al, 2021b). In lipopolysaccharide (LPS)-induced human renal proximal tubular cells, rosiglitazone (an agonist of PPARγ) decreases chemokines expression via inhibiting NF-κB activation by activating PPARγ SUMOylation (Lu et al, 2013).…”
Section: Nf-κb Signalingmentioning
confidence: 99%